Sociology in Morality and Its Priority on Sociology of Morality - Sadeghi, Masoud; ., . (International Journal of Engineering and Technology, 2018)
In this paper, the subject of sociology of morality and its main issues are examined. Topics such as relation between class and moralityØŒ power and moralityØŒ economy and moralityØŒ ideal ethics and real ethics and relation between ethics and traditional society and modern Society. In the next step meaning of sociology of morality separated from sociology of ethical knowledge and finally meaning of â€œsociology in morality â€, as most innovative part of paper for the first time defined, and justified.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â